2005
DOI: 10.1148/radiol.2362040984
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of US and Unenhanced Multi–Detector Row CT in Patients Suspected of having Acute Appendicitis

Abstract: Although the diagnostic performances of US and multi-detector row CT are comparable, more inconclusive images were obtained with US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(32 citation statements)
references
References 26 publications
2
27
1
2
Order By: Relevance
“…Although a 7.5 MHz probe with an annular array transducer was generally used, a 5 MHz convex probe was also employed depending on the patient's physique and the depth of the appendix. On the basis of ultrasonograph findings, appendicitis was classified as follows: catarrhal (appendix was tubular with a clear layer structure of the appendiceal wall, slight mucosal oedema, and a maximum transverse diameter of 10 mm); phlegmonous (ill-defined layer structure of the appendix wall, moderate enlargement of the appendix, and a maximum transverse diameter of 10 mm); gangrenous (illdefined or unidentifiable layer structure of the appendiceal wall and severe enlargement of the appendix to form a mass) [13].…”
Section: Data Collectionmentioning
confidence: 99%
“…Although a 7.5 MHz probe with an annular array transducer was generally used, a 5 MHz convex probe was also employed depending on the patient's physique and the depth of the appendix. On the basis of ultrasonograph findings, appendicitis was classified as follows: catarrhal (appendix was tubular with a clear layer structure of the appendiceal wall, slight mucosal oedema, and a maximum transverse diameter of 10 mm); phlegmonous (ill-defined layer structure of the appendix wall, moderate enlargement of the appendix, and a maximum transverse diameter of 10 mm); gangrenous (illdefined or unidentifiable layer structure of the appendiceal wall and severe enlargement of the appendix to form a mass) [13].…”
Section: Data Collectionmentioning
confidence: 99%
“…contrast enhanced CT in this setting, but limited in its sensitivity [6,10,12,15,17]. Others reported that ultrasound achieves similar results to unenhanced CT, but is mainly restricted by a large number of indeterminate cases [18].…”
Section: Introductionmentioning
confidence: 99%
“…Because acute appendicitis is a common abdominal emergency affecting young adults, the high amount of radiation dose delivered by abdominal CT raises a major concern with regard to its systematic use as the first-line examination tool in this population [10,11]. To reduce the radiation dose, some authors suggest that sonography should be the initial screening of patients with suspicion of appendicitis [12][13][14][15]. However, in spite of the fact that, in skilled hands, sonography has been reported to be highly specific in the depiction of appendicitis, it is limited by a high rate of false negative or indeterminate results [16][17][18].…”
Section: Introductionmentioning
confidence: 99%